From the cell system to the electronic surveillance system. Changes in the execution of the custodial penalty - Nikołajew, Jerzy (The Opole Studies in Administration and Law, 2020)
The evolution of the methods for execution of the custodial penalty demonstrates changes in the treatment of convicts. In the historically oldest systems, the aspect of subjectivity of convicts was completely omitted in favour of their complete isolation (objectification), which resulted in the lack of corrective effects. It was only later that the system of progression in its various forms was adopted, which allowed strengthening of the convicts’ position by appreciation of their work and education as well as gradual mitigation of the effects of prison isolation. Finally, the concept of executing a penalty outside the prison in the electronic surveillance system was adopted, which departed from the absolute necessity of imprisonment towards more socially effective probation measures.